usun niewymiernosc z mianownika
a)
[tex] \frac{12}{ \sqrt{3} } [/tex]
b)
[tex] \frac{ - 2 \sqrt{15} }{3 \sqrt{5} } [/tex]


Odpowiedź :

[tex]a) \ \frac{12}{\sqrt{3}} = \frac{12}{\sqrt{3}}\cdot\frac{\sqrt{3}}{\sqrt{3}} = \frac{12\sqrt{3}}{3} = 4\sqrt{3}\\\\b) \ \frac{-2\sqrt{15}}{3\sqrt{5}} = \frac{-2\sqrt{15}}{3\sqrt{5}}\cdot\frac{\sqrt{5}}{\sqrt{5}} =-\frac{2\sqrt{15\cdot5}}{3\cdot5} =-\frac{2\sqrt{75}}{15} = -\frac{2\sqrt{25\cdot3}}{15} = -\frac{2\cdot5\sqrt{3}}{15} = -\frac{2\sqrt{3}}{3}[/tex]

Odpowiedź:

a)

12/√3 = 12/√3 * √3/√3 = 12√3 : 3 = 4√3

b)

-2√15/(3√5) = -2/3 * √15/5 = -2/3 * √3

Szczegółowe wyjaśnienie:

Viz Inne Pytanie